Poligami Dalam Perspektif Hadis - junaid, hamzah (An - Nisa`, 2012)
Abstract: This article examines, This article analyzes polygamy in hadits perspective. Hadith are all the words, deeds and taqrir of prophet Muhammad. Through this article, it is understood that islam is basically advocating polygamyÂ  much less require, but islam simply passes on the permissibility of polygamy, and that was a small possibility that can only be traversed by anyone who really need and there quire mentis not mild.Based on information from the hadith, one of the requirements to be met by a polygamist who want to do it namely the ability to be fairÂ  to his wives. Therefore, permission for polygamy is only given to those who suspect that the steps that he take can please all the wives whom he married at least a man can do justice to his wife.Another requirement that must be met by a husband is the husband should go to his wives in turn for the realization of happiness. By this way, the justice will be realized, and that is what was practiced by the prophet Muhammad and his friends.